Development of biosimilars in an era of oncologic drug shortages - Li E; Subramanian J; Anderson S; Thomas D; McKinley J; Jacobs IA (Dove Medical Press, 2015)
Edward Li,1 Janakiraman Subramanian,2 Scott Anderson,3 Dolca Thomas,4 Jason McKinley,5 Ira A Jacobs4 1University of New England College of Pharmacy, Portland, ME, USA; 2Hanna Cancer Associates, Knoxville, TN, USA; 3Pfizer Inc, La Jolla, CA, USA; 4Pfizer Inc, New York, NY, USA; 5Pfizer Inc, Groton, CT, USA Abstract: Acute and chronic shortages of various pharmaceuticals and particularly of sterile injectable products are being reported on a global scale, prompting evaluation of more effective strategies to manage current shortages and development of new, high-quality pharmaceutical products to mitigate the risk of potential future shortages. Oncology drugs such as liposomal doxorubicin and 5-fluorouracil represent examples of first-choice drugs critically affected by shortages. Survey results indicate that the majority of hospitals and practicing oncologists have experienced drug shortages, which may have compromised patient safety and clinical outcomes, and increased health care costs, due to delays or changes in treatment regimens. Clinical trials evaluating novel agents in combination with standard-of-care drugs are also being affected by drug shortages. Clinical and ethical considerations on treatment objectives, drug indication, and availability of alternative options may help in prioritizing cancer patients involved in active drug shortages. The United States Food and Drug Administration and the European Medicines Agency have identified manufacturing problems, delays in supply, and lack of available active ingredients as the most frequent causes of recent or ongoing drug shortages, and have released specific guidance to monitor, manage, and reduce the risk of shortages. The upcoming loss of exclusivity for a number of anticancer biologics, together with the introduction of an abbreviated approval pathway for biosimilars, raises the question of whether these products will be vulnerable to shortages. Future supply by reliable manufacturers of well characterized biosimilar monoclonal antibodies, developed in compliance with regulatory and manufacturing guidelines and with substantial investments, may contribute to prevent future biologics shortages and ensure access to effective and safe treatment options for patients with cancer. Preclinical and clinical characterization is ongoing for potential biosimilars of trastuzumab, rituximab, and bevacizumab, with promising results. Keywords: biologics, monoclonal antibody, cancer, rituximab, safety, trastuzumab